تطبيق وسيلة تعليم اللغة العربية “Learn With Farhan” لترقية مهارة القراءة والكتابة لدى طلاب الفصل الحادي عشر بالمدرسة الثانوية الإسلامية الحكومية سورابايا - Aulyaa, Muhammad Habiibul; Al Farisi , Mohamad Zaka; Nandes, Rio (Lisanudhad: Jurnal Bahasa, Pembelajaran, dan Sastra Arab, 2024)
Understanding Al-Furūq  Al- Lugawiyyah in Arabic is very important for learners to avoid the misuse of synonyms. However, many learners still have difficulty in understanding the difference of meaning and the proper use of synonyms. This study aims to design an Al-Furūq  Al- Lugawiyyah dictionary that focuses on vocabulary that is often used in everyday life. The research method used is Research and Development (R&D) with the ADDIE model, but this research only concentrates on the Analysis and Design stages. The data collection method is through observation and interviews conducted at STIBA Ar-Raayah Sukabumi, and also refers to books and scientific works related to research. This research resulted in the design of a dictionary that could add to the understanding of Al-Furūq Al- Lugawiyyah by showing significant differences in meaning and usage between synonymous words such as أب and, والد   أعادandعودة, كرر  and رجوع and others. This dictionary is designed with Arabic-Indonesian bilingual, arranged alphabetically and equipped with explanations of differences in meaning, examples of use, and references from the Qur'an and Hadith. However, in the design of this dictionary, the author only includes 50 vocabularies, so the author hopes that further research can produce a dictionary with a larger number of vocabularies.